Probing local and global ferroelectric phase stability and polarization switching in ordered macroporous PZT - Mclachlan,MA; McComb,DW; Ryan,MP; Morozovska,AN; Eliseev,EA; Payzant,EA; Jesse,S; Seal4,K; Baddorf,AP; Kalinin,SV (Advanced Functional Materials, 2011)
We describe the characterization, ferroelectric phase stability and polarization switching in strain-free assemblies of PbZr0.3Ti0.7O3 (PZT) nanostructures. The 3-dimensionally ordered macroporous structures present uniquely large areas and volumes of PZT where the microstructure is spatially modulated and the composition is homogeneous. Variable temperature powder X-ray diffraction (XRD) studies show that the global structure is crystalline and tetragonal at room temperature and undergoes a reversible tetragonal to cubic phase transition on heating/cooling. The measured phase-transition temperature is 50 – 60 °C lower than bulk PZT of the same composition. The local ferroelectric properties were assessed using piezoresponse force spectroscopy that reveal an enhanced piezoresponse from the nanostructured films and demonstrate that the switching polarization can be spatially mapped across these structures. An enhanced piezoresponse is observed in the nanostructured films which we attribute to the formation of strain free films, thus for the first time we are able to assess the effects of crystallite-size independently of internal stress. Corresponding polarization distributions have been calculated for the bulk and nanostructured materials using a direct variational method and Landau-Ginzburg-Devonshire (LGD) theory. By correlating local and global characterisation techniques we have for the first time unambiguously demonstrated the formation of tetragonal and ferroelectric PZT in large volume nanostructured architectures. With the wide range of materials available that can be formed into such controlled architectures we conclude that this study opens a pathway for the effective studies of nanoscale ferroelectrics in uniquely large volumes